SOCIAL MEDIA SENTIMENT AND STOCK PRICE REACTION: AN ACCOUNTING PERSPECTIVE - Rina Nopianti; Prastika Suwandi Tjeng; D Muhamad Yamin (CV. Adiba Aisha Amira, 2026)
The development of social media has transformed the financial information landscape by providing non-traditional data sources that increasingly influence capital market behavior. Information generated by social media users, particularly in the form of public sentiment toward companies, serves as an important signal that can influence investor perceptions and stock price reactions. This study aims to systematically examine the relationship between social media sentiment and stock price reactions from an accounting perspective using a literature review method. This study examines empirical findings from various previous studies that discuss the role of social media sentiment in influencing stock price volatility, abnormal returns, trading volume, and its relevance to the quality and timeliness of accounting information. The results indicate that positive and negative sentiment on social media can significantly influence market reactions, particularly during periods surrounding financial information announcements and significant corporate events. From an accounting perspective, social media sentiment serves as a complement to traditional accounting information by increasing the information content relevant to investor decision-making. However, the literature review also reveals challenges related to information bias, source credibility, and potential information asymmetry that can influence investor interpretation. This research provides theoretical contributions by broadening the understanding of the integration of social media-based information within accounting and capital markets, as well as practical implications for accountants, financial analysts, and regulators in responding to the dynamics of digital information in the modern financial market era.